Persistence of individual and social preferences in rural settings - Castillo, José Gabriel; Hernandez, Manuel A. (International Food Policy Research Institute, 2025)
Preferences play a key role in decision-making and are generally assumed as time-invariant in economic modeling despite the mixed empirical evidence. We examine the stability of individual and social preferences in rural settings using the COVID-19 pandemic as a major global shock. We employ a unique longitudinal dataset comprising 1,262 smallholder households, based on interviews with household heads conducted across four survey waves between 2019 and 2022. We find a temporal, two-year shift in risk tolerance, while interpersonal trust and generosity perceptions show a sustained deterioration over three years. We explore possible variations by household characteristics and the degree of exposure to the virus, self-confinement, and extreme weather events.